2021
DOI: 10.3390/molecules26216483
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Stability of Ocimum basilicum Essential Oil and Its Major Components in the Control of Sitophilus zeamais

Abstract: Essential oils (EOs) are widely recognized as efficient and safe alternatives for controlling pest insects in foods. However, there is a lack of studies evaluating the toxicological stability of botanical insecticides in stored grains in order to establish criteria of use and ensure your efficiency. The objective of this work was to evaluate the toxicological stability of basil essential oil (O. basilicum) and its linalool and estragole components for Sitophilus zeamais (Motschulsky) adults in corn grains by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…A gas chromatograph–mass spectrometer model QP2010 (Shimadzu, Tokyo, Japan) equipped with an autosampler and autoinjector (AOC-20si) was used for this study. The procedures for injection, separation, and identification of compounds, as well as the temperature of the column oven, were based on previous reports with some modifications [ 58 , 59 ]. The essential oil was dissolved in hexane (10 mg/mL), and the system was operated at 70 eV.…”
Section: Methodsmentioning
confidence: 99%
“…A gas chromatograph–mass spectrometer model QP2010 (Shimadzu, Tokyo, Japan) equipped with an autosampler and autoinjector (AOC-20si) was used for this study. The procedures for injection, separation, and identification of compounds, as well as the temperature of the column oven, were based on previous reports with some modifications [ 58 , 59 ]. The essential oil was dissolved in hexane (10 mg/mL), and the system was operated at 70 eV.…”
Section: Methodsmentioning
confidence: 99%
“…The LC 50 values at 15 °C were estimated as 19.3, 16.9 and 27.1 μL L −1 air and were estimated at 30 °C as 24.4, 33.9 and 27.1 μL L −1 air, respectively, for the EO, thymol and carvacrol. Furthermore, Moura et al 42 displayed that light affects negatively the stability of Ocimum basilicum EO and decreases the toxicity against Sitophilus zeamais population. Numerous modern technological innovations involving different delivery systems have been explored to reduce these defects.…”
Section: Release Studiesmentioning
confidence: 99%
“…basilicum is mainly composed of linalool and estragole, its toxicity can be explained by the action of the mixed activity of the enzyme acetylcholinesterase (AChE), especially when they are applied by fumigation. Namely, a study on corn grains showed that the increase in temperature (35 °C) and exposure to light during processing affected the stability of this EO (Moura et al, 2021).…”
Section: Essential Oils In the Control Of Acanthoscelides Obtectusmentioning
confidence: 99%